Genomics-Based Insights Into the Biosynthesis and Unusually High Accumulation of Free Fatty Acids by Streptomyces sp. NP10 - Schneider, Olha; Ilic-Tomic, Tatjana; Rückert, Christian; Kalinowski, Jörn; Genčić, Marija S.; Živković, Milena Z.; Stankovic, Nada; Radulović, Niko S.; Vasiljevic, Branka; Nikodinovic-Runic, Jasmina; Zotchev, Sergey B. (Frontiers in Microbiology, 2018)
Streptomyces sp. NP10 was previously shown to synthesize large amounts of free fatty acids (FFAs). In this work, we report the first insights into the biosynthesis of these fatty acids gained after genome sequencing and identification of the genes involved. Analysis of the Streptomyces sp. NP10 draft genome revealed that it is closely related to several strains of S. griseus. Comparative analyses of secondary metabolite biosynthetic gene clusters, as well as those presumably involved in fatty acid biosynthesis, allowed identification of an unusual cluster C12-2, which could be identified in only one other S. griseus-related streptomycete. To prove the involvement of identified cluster in FFA biosynthesis, one of its three ketosynthase genes was insertionally inactivated to generate mutant strain mNP10. Accumulation of FFAs in mNP10 was almost completely abolished, reaching less than 0.01% compared to the wild-type strain. Cloning and transfer of the C12-2 cluster to the mNP10 mutant partially restored FFA production, albeit to a low level. The discovery of this rare FFA biosynthesis cluster opens possibilities for detailed characterization of the roles of individual genes and their products in the biosynthesis of FFAs in NP10.